Peran Sektor Publik dalam Akumulasi Human Capital dan Kapasitas Research & Development - Sanjoyo Sanjoyo (STIE Indonesia Banking School, 2016)
In the theory of economic growth, sources of economic growth, sources of growth comes from the ability of a country in developing potential resources. Quality and the greater the higher the quality of resources, it also has a greater potential to increase a country’s economic growth. Factors that are important in sources of growth are natural resources, capital, saving, and development of technology. Property natural resources would help the economy of a country, although not enough if not supported by the skill of exploration for natural resources. Both capital and saving is also a factor of production as the dominant element of economic growth for the future. Similarly, the development of technology can be widely accepted as a source of economic growth. This is because the technology that allows manufacturers to produce more with the same input level. The development of technology depends on the ability of science and the quality of education of a country and how much attention on research and development. Results of empirical studies of economic growth showed that the relationship is a strong economic development of a country with a capacity of human capital in the country. However, the dynamic relationship between economic growth with human capital and research & development can be explained since 1980 when Romer and Lucas describe the relationship with the growth model endogenous or new growth theory. In this paper will try to explain briefly the history of the development of the economics of growth theory and briefly review the core of neoclassical model and endogenous growth models. Then, this paper will explain the role of accumulation of human capital and research & development in economic development. Finally, this paper will review the role of the public sector and policy implications in the process of accumulation of human capital and investment of R & D to contribute to economic growth.